Recurrent hypoglycemia and a slowly rising hemidiaphragm: A case report - Vincent Simpson; Andrew McGovern (Clinical Case Reports, 2021)
Abstract Non‐islet cell tumor hypoglycemia should be considered in unexplained recurrent non‐insulin‐dependent hypoglycemia. Where surgery is not possible steroids may be effective, even at low dose, at managing hypoglycaemia.